Geographical and disciplinary coverage of open access journals: OpenAlex, Scopus, and WoS - Abdelghani Maddi; Marion Maisonobe; Chérifa Boukacem-Zeghmouri (PLoS ONE, 2025)
This study aims to compare the geographical and disciplinary coverage of OA journals in three databases: OpenAlex, Scopus and the Web of Science (WoS). We used the Directory of Open Access Scholarly Resources (ROAD), provided by the ISSN International Centre, as a reference to identify OA active journals (as of May 2024). Among the 62,701 active OA journals listed in ROAD, the WoS indexes 6,157 journals, Scopus indexes 7,351, while OpenAlex indexes 34,217. A striking observation is the presence of 24,976 OA journals exclusively in OpenAlex, whereas only 182 journals are exclusively present in the WoS and 373 in Scopus. The geographical analysis focuses on two levels: continents and countries. As for disciplinary comparison, we use the ten disciplinary levels of the ROAD database. Moreover, our findings reveal a similarity in OA journal coverage between the WoS and Scopus. However, while OpenAlex offers better inclusivity and indexing, it is not without biases. The WoS and Scopus predictably favor journals from Europe, North America and Oceania. Although OpenAlex presents a much more balanced indexing, certain regions and countries remain relatively underrepresented. Typically, Africa is proportionally as under-represented in OpenAlex as it is in Scopus, and some emerging countries are proportionally less represented in OpenAlex than in the WoS and Scopus. These results underscore a marked similarity in OA journal indexing between WoS and Scopus, while OpenAlex aligns more closely with the distribution observed in the ROAD database, although it also exhibits some representational biases.